On Life and Death of Squares. A dialogue between architect Elena Bagina and designer Leonid Salmin - Bagina, Elena (project baikal, 2018)
Metamorphoses of social life in the USSR in the 20th century occurred so impetuously that the ‘link of times’ supported by architecture of squares was broken. The imperial squares of the Soviet period in Russia, that replaced the cathedral squares, have lost their former mission and failed to find a new life. The attempt to artificially revitalize those squares fails for many reasons: a huge scale, overloading with transport, lack of places of attraction, and new buildings mismatching the character of former development and composition. Installation of swings and benches does not save the situation. It only underlines the inharmony of such designs. There are no squares in the projects for new residential areas. They are replaced by shopping and entertainment malls, which look like giant storehouses.